2016
DOI: 10.1108/ijse-03-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Bank risk-taking in the MENA region

Abstract: Purpose The purpose of this paper is to investigate determinants of risk-taking in Islamic banks and conventional banks located in the MENA region. Design/methodology/approach The empirical study covers a sample of 15 conventional and 15 Islamic banks for the period 2002-2009. The authors estimate models using both generalized least square random effect and generalized method of moments system approaches. Findings The results of the empirical analysis show that the determinants’ risk-taking significance va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 59 publications
1
27
0
3
Order By: Relevance
“…They justified their findings by stating that high capital requirements could constrain banks from taking a high risk. Similarly, Selma-Mokni, Rajhi and Rachdi (2016) analysed the data of 30 commercial banks in the MENA region. They concluded that capital adequacy ratios and investment in risky assets were significantly and negatively associated.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…They justified their findings by stating that high capital requirements could constrain banks from taking a high risk. Similarly, Selma-Mokni, Rajhi and Rachdi (2016) analysed the data of 30 commercial banks in the MENA region. They concluded that capital adequacy ratios and investment in risky assets were significantly and negatively associated.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…In addition, the Z-score is used to measure bank's default and assess its bankruptcy (Demirgiic & Huizinga, 1999;Khan et al, 2017;Mokni et al, 2016). Z score is also used to measure the ability of capital and income to cover losses in a certain period (Lepetit & Strobel, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alharthi (2017) described the quoted Islamic banks as being more stable than the unquoted Islamic banks and the banks listed had lower capitals as well. Mokni, Rajhi and Rachdi (2016) empirically found that MENA Islamic banks are less stable than conventional banks, and that they also have determinants of risk-taking. Abedifar, Molyneux and Tarazi (2013), Chakroun and Gallali (2013), and Čihák and Hesse (2010) analysed the risk of insolvency using the Z-score measurement usually found that small conventional banks have high default risk compared to small Islamic banks.…”
Section: Islamic Banks and Insolvency Riskmentioning
confidence: 99%
“…As for example, Khan and Ahmad (2001) remarked the inherent risk such as the credit risk of the Islamic banks which adopted interest rate as much as KLIBOR among the Malaysian Islamic banks. This situation encourages the Islamic banks giving too many loans to less creditworthy borrowers (Mokni, Rajhi, & Rachdi, 2016). In addition, liquidity risk, which is another type of risk owned by the Islamic banks, affects the capability of Islamic banks to fulfill their liability.…”
Section: Introductionmentioning
confidence: 99%